Pre-Service Early Childhood Educators’ Perspectives on Music, Dance, and Drama for Children with Special Educational Needs in Malaysia - Suhaila Mohamad (SEA-CECCEP, 2025)
Music, dance, and drama are increasingly recognised as powerful pedagogical tools in early childhood education (ECE), fostering creativity, confidence, collaboration, and inclusivity. However, despite policy commitments to inclusion, limited attention has been given to how these art forms can be systematically embedded into teacher preparation, particularly to support children with Special Educational Needs (SEN). This study addressed this gap by examining three questions: (1) How do future early childhood educators perceive the role of music, dance, and drama in enhancing creativity, confidence, and collaboration? (2) In what ways do these art forms contribute to classroom readiness for inclusive practice? and (3) How do pre-service educators understand their potential in fostering inclusion, particularly for children with SEN? Adopting a mixed-methods design, data were collected from 62 undergraduate pre-service early childhood educators through surveys and open-ended reflections. Quantitative findings, analysed using descriptive statistics, indicated strong agreement that music, dance, and drama enhance creativity, build confidence, strengthen collaboration, and prepare educators for diverse classrooms. Qualitative insights reinforced these perspectives, highlighting benefits such as multisensory engagement, empathy-building, and adaptability, while also identifying barriers including limited training, insufficient resources, and few structured opportunities for practice. The study concludes that music, dance, and drama should be positioned as central rather than peripheral within inclusive pedagogy in ECE. Recommendations include embedding these art forms into teacher education coursework and workshops, as well as strengthening institutional support through resources and arts-based partnerships. These findings align with the vision of an equitable, high-quality ECE, positioning music, dance, and drama as transformative tools for inclusive practice across Southeast Asia.